Referred otalgia:evaluation of causes - Ali Fleah, Khalid (Tikrit Journal of Pharmaceutical Sciences, 2023)
Otalgia is the sensation of pain in the car, while referred otalgia Is pam felt in the ear but originating from non-otological source Lar pain is a diagnostic problem when examination of the ear shows no pathology. A prospective study was conducted in EN.T - private clinics in Kirkuk city from October 2007 to December 2008. Age , sex and causes of referred ofalgia were noted, During the study period 210 patients were evaluated , out of 210 patients 122 male "58%" and 88 females "42%", Tonsillitis,pharyngitis and post tonsillectomy were the commonest cause"S1 4%" Three patients had malignancy of upper aerodigestive tract and referred otalgia was one of its main symptoms. Referred ear pain is more commonly caused by tonsillitis , pharyngitis but it may be first symplom of head and neck malignancy,